Are the Tanjung Puting National Park as an Alternative to Ecotourism-based Sustainable Development? - Irawan; Andrie Elia (Emerging Issues in Environment, Geography and Earth Science Vol. 2, 2023)
The goal of the study is to identify and quantify the determining elements for Tanjung Putting National Park’s sustainable ecotourism development. Survey and observational methods are used to gather data on both exogenous and endogenous factors utilizing a questionnaire. The rapid development of eco-tourism (ecotourism), as one of the tourism industries with the potential to increase the revenue of the country, especially in the last decade. Tanjung Putting Park, in the province of Central Kalimantan, is the site of the research, which was done from May to July 2019. Both local and international tourists that visited Tanjung Putting National Park make up the study’s population. Both primary and secondary data were used. The sample size for the convenience sampling methods used in nonprobability sampling [1], was 250 respondents. Analysis tool that uses statistical analysis of test models Path Analysis. The results showed (1) the development of tourism products such as transportation, home stay and tourist attractions like feeding orangutans as well as the environmental uniqueness of tropical forest and blackwater areas have a significant influence on the amount of tourist visits and the length of stay of tourists in ecotourism areas, (2) the development of tourism products and uniqueness The environment has a significant influence on the development and utilization of sustainable ecotourism. (3) Based on the first two conclusions, it is stated that Tanjung Putting National Park can be an alternative for sustainable ecotourism development.